Influence of Fine-Dining Restaurant Service Quality and Legitimacy on Revisit Intentions in Tshwane City, South Africa - Basera, Clay Hutama; de Jager, Johan W.; Drotsky, Antonie (International Review of Management and Marketing, 2026)
The aim of the study was to examine the influence of service quality dimensions and legitimacy on consumer revisit intentions in Tshwane city’s fine-dining restaurants. The study was grounded in the DINESERV and Institutional theoretical frameworks. The study adopted a quantitative descriptive cross-sectional inquiry that surveyed participants once. Cconvenience sampling was employed via online platforms to distribute questionnaires to two hundred and twenty participants. Of these, one hundred and eighty four were suitable for analysis. The questionnaire required participants to choose their responses based on a non-comparative five-point Likert scale. Descriptive and inferential statistics were utilised as modes of statistical analyses. Structural equation modelling using SmartPLS4 was adopted. The results revealed that empathy, employee service quality, food quality, hygienic practices and safety assurance had insignificant positive influence on both pragmatic and social legitimacy. However, although physical environmental quality insignificantly influenced pragmatic legitimacy, its influence on social legitimacy was positively significant and more interestingly, responsiveness and reliability had significant positive influence on both forms of legitimacy. Therefore, managers and practitioners in the fine-dining restaurant sector should realise that unparalleled service quality does not warrant legitimacy and that other factors other than legitimacy are important drivers of consumer revisit intentions.